1993
DOI: 10.1177/000486589302600103
|View full text |Cite
|
Sign up to set email alerts
|

Homicide Between Adult Sexual Intimates: A Research Agenda

Abstract: Little research that focuses upon homicide-suicides between adult sexual intimates has been conducted to date. Yet U.S., U.K., and Australian studies on homicide and homicidesuicide show that a disproportionate number of those that kill and subsequently take their own lives are the husbands or estranged sexual intimates of their victims. This paper provides some retrospective data on the historical, demographic, and situational traits of this type of homicide-suicide in Australia by looking at what, if anythin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 29 publications
6
52
1
Order By: Relevance
“…However, on the other hand, Easteal (1994) and Selkin (1976) found that the backgrounds of HS offenders were as deviant as ordinary homicide offenders. They also found hostility in the majority of events in their samples.…”
Section: Offender Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, on the other hand, Easteal (1994) and Selkin (1976) found that the backgrounds of HS offenders were as deviant as ordinary homicide offenders. They also found hostility in the majority of events in their samples.…”
Section: Offender Characteristicsmentioning
confidence: 99%
“…Nevertheless, the HS phenomenon is far from homogenous, and not infrequently an HS event is dominated by the theme of revenge (Easteal 1994;Henry and Short 1954;Selkin 1976;Rosenbaum 1990;Wolfgang 1958). Wolfgang (1958) compared homicide-only and HS events in Philadelphia and found that HS offenders were as least as hostile as homicideonly offenders.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this type of patient, better risk assessment during ''highrisk time'' (certain periods of Spring and Summer, periods around major public holidays) might allow external treatment and care decisions and cycles to be timed more sensitively. Case reports indicate that in some circumstances, better assessment of psychiatric patients could indeed have prevented tragedy [Easteal, 1994].…”
Section: Clinical Relevance Of Findings and Implications For Researchmentioning
confidence: 99%